Ivermectin and its synthetic derivatives - A new class of anticancer agents - Michał Sulik; Dagmara Otto-Ślusarczyk; Michał Antoszczak; Marta Struga; Adam Huczyński (Elsevier, 2024)
Ivermectin (IVR) is a 16-membered macrocyclic lactone of Nobel prize-honored distinction, showing a broad spectrum of biological activity, especially antiparasitic. We have recently designed a practical and scalable procedure for the synthesis of IVR derivatives with a rearranged oxahydrindene (hexahydrobenzofuran) ring that revealed improved antiparasitic activity compared to that of the native structure. Of note, the compounds that show activity towards parasites, very often are active against cancer cells and vice versa. However, the anticancer potential of IVR has not been studied intensively as yet, and there have been no reports on the effects of its synthetic derivatives against cancer cells. Thus, in the study reported, we thoroughly investigated the anticancer activity of IVR and its derivatives against a panel of four human cancer cell lines. We have identified a number of IVR derivatives with improved cytotoxicity and/or cancer cell-targeting selectivity compared to those of reference compounds. Cell cycle analysis has proved that selected compounds increased the number of cancer cells in the subG1 and G0/G1 phases (PC3, MDA-MB-231 and A549) or S/G2/M phase (HCT-116). The strong proapoptotic effect observed for the most promising IVR derivatives has been associated with a significant increase in caspase-3/7 activation and reactive oxygen species (ROS) production. Finally, these derivatives also showed significant inhibition of interleukin-6 (IL-6) cytokine secretion in cancer cells used. Our results indicate that chemical modification of IVR can lead to synthetic products with enhanced anticancer activity, which may provide an excellent starting point for further development of new IVR-derived agents for the treatment against cancer cells.